Analysis of Youth Interest in Work as Sheep Farmers at P4S LKP2U - M. Yusuf; L. Cyrilla; H. Nuraini; T. U. P. Sujarnoko (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
An increase in the number of demands for lamb meat every year represents livestock business opportunity while the supply from smallholder farmers continues to decline, causing prices to rise yearly. Sustainability is important in the sheep farming business, which older farmer dominated. The objective of this research was to assess the inclination of the younger population towards pursuing careers as sheep farmers after participating at the Pusat Pelatihan Pertanian Pedesaan Swadaya (P4S) of Lembaga Kajian dan Pengembangan Potensi Umat (LKP2U) program in the Madiun Regency. Novelty of the research is the presentation of the latest information on youth interest in working as a farmer. Data collection was carried out in December 2022 using non-probability sampling. The data in this study were analyzed using a Likert scale to measure entrepreneurial interest and demographic factors. Furthermore, a binary logistic regression analysis was conducted to determine the relationship between the predictor and response variables. Youth interest after participating in the training program chooses an interest in working as a sheep farmer at 70%. Factors that influence youth interest after attending the training program towards employment as a sheep farmer are demographic factors namely age, marital status, duration of education, parents occupation, parents income, family members, and entrepreneurial factors (e.g personal, environmental, and social).